Executive Compensation, Ownership Structure and Dividend Payout: Evidence from Malaysia - Ravichandran K. Subramaniam,; Teh Chee Ghee,; Murugasu Thangarajah, (Asian Academy of Management Journal of Accounting and Finance, 2020)
This study seeks to present the relationship between executive compensation, dividend payout policy and ownership structure of listed firms in Malaysia. We examine a panel data on a sample of 300 of the largest Malaysian public listed companies (PLCs) on Bursa Malaysia for the years 2008 to 2014. Based on 2,009 firm-year observations, our results show consistent empirical positive evidence on the association between dividend payout and executive compensation across all models. However, the results are inconsistent with Bhattacharyya model of dividend payout. Further, there is evidence that government and family ownerships are positively associated with dividend payout. Our results show that the positive relationship between executive compensation and dividend payout is more evident in politically connected firms (PCON firms) which is consistent with the clientele (catering) theory.